Inter/multi/transdisciplinarity : Bridging Differences in ‘Cultures of Knowledge’ - Žic Fuchs, Milena (Array, 2014)
The ideas behind this title cover the changes in the European Research Areas encapsulated in HORIZON 2020, which through its Grand Challenges or Societal Challenges, as they are now called, by default imply a global perspective. What follows is that addressing issues such as climate change, personalized medicine, demographic change, etc., cannot be solved without a global perspective that without doubt includes a major scientific force like China. What is more, the Grand Challenges cannot be addressed without the Social Sciences and Humanities, and this in turn involves different approaches and traditions of research, and different ‘cultures of knowledge’. It also involves rethinking the “human element” in new contexts embedded in cultures diverse in many respects. The question this paper aims to address is how do we bridge these differences?